A Fracture Toughness Test Using the Ball‐on‐Three‐Balls Test. Issue 1 (3rd October 2015) - Lube, Tanja; Rasche, Stefan; Nindhia, Tjokorda Gde Tirta
Abstract : A method for fracture toughness measurement of ceramics using small disks and plates is presented. Similar to the surface‐crack‐in‐flexure (SCF) method a semielliptical surface crack is introduced centrally into one plane side of the specimen which is fractured in a ball‐on‐three‐balls test. Finite element simulations are used to evaluate the stress intensity factor (SIF) for this loading geometry for a range of crack sizes and crack geometries. Empirical formulae for the geometric function are provided for evaluation of the test. The effect of position uncertainties is investigated using FEM and experiments. Other sources which may contribute to the measurement error are identified and quantified, resulting in recommendations for the practical realization of the test. A determination of the fracture toughness within ±10% measurement uncertainty is possible with specimens larger than 8 mm in diameter and thicker than 0.5 mm. With larger specimens an uncertainty comparable to other fracture toughness tests can be achieved. For precise measurements it is important to position the crack within ±120 μm of the stress maximum, to know Poisson's ratio exactly and to test cracks that have the maximum SIF at their deepest point. A method how this can be achieved is presented.